Emergency Surgery for Colon Diseases in Elderly Patients—Analysis of Complications, and Postoperative Course - Mario Pacilli; Alberto Fersini; Giovanna Pavone; Pasquale Cianci; Antonio Ambrosi; Nicola Tartaglia (Medicina, 2022)
Background and Objectives: Colon diseases can turn in a clinical emergency with the onset of some important complications. Some critical conditions are more common in aged patients because they are frailer. The aim of this study is to examine patients over 80 years of age who are undergoing emergency colorectal surgery, and evaluating the aspects associated with post-operative complications and other problems in the short term. Methods: From November 2020 to February 2022, we included 32 consecutive patients older than 80 undergoing emergency surgery due to colon diseases. We collected and analysed all demographic and operative data, and then applied CR-POSSUM score and correlated this with postoperative hospital stay and the onset of postoperative complications according to the Clavien Dindo classification. Results: Postoperative factors were selectively evaluated based on the clinical scenario and different colic pathologies. There were no statistically significant differences, in terms of postoperative hospital stay, postoperative complications, reoperation rate and 30-day mortality. The number of cases of blood transfusions was significant and was more numerous in cases of intestinal perforation and bleeding cases. The value of the Operative Severity Score in bowel perforations was significantly higher. Conclusions: The use of a score to stratify the risk is a useful tool, especially in elderly patients undergoing emergency surgery. The CR-POSSUM score was important for predicting morbidity in our study. Emergency manifestations of colon diseases in the elderly show higher morbidity and mortality rates. The effect of age on outcome is a concept that needs to be emphasized, so further investigation is needed.